Analysis of Soil Replacement and Woven Geotextile Reinforcement on Embankment Stability - Agustina, Yani Putri; Handiman, Iman; Sarifah, Fitriana; Hamonangan, Efran Kemala; Irawan, Pengki; Gusnadi, Zakwan (invotek, 2024)
Toll roads are infrastructure built to improve the regional and national economy. The challenge faced on this toll road is soft soil as deep as 7 m. This research analyzes the stability of the embankment with a slope of 1V:2H and a height of 4.5 m without and with repair using the Limit Equilibrium Method (LEM) because the Safety Factor (SF) value in LEM provides a more critical value than the Finite Element Method (FEM). In addition, the settlement amount was also analyzed. The SF value in short term conditions with an embankment load of 1.31 < 1.4 and earthquake load of 0.83 < 1.1. Then, at pavement installation, 1.33 < 1.4, plus earthquake load 0.84 < 1.1. In long term conditions, during the operational period, 1.48 < 1.5, plus earthquake load 0.84 < 1.1. This indicates that the soil requires improvement. To address the problem, soil improvement utilized 2.5 m deep soil replacement and 75 kN woven geotextile. The SF value with repair under short term conditions, with embankment load 1.53 > 1.4, plus earthquake load 1.18 > 1.1. Then, at the time of pavement installation, 1.56 > 1.5, plus earthquake load 1.19 > 1.1. In the long term condition, it was 1.62 > 1.5 at the time of operation, plus earthquake load 1.22 > 1.1. The total settlement after the operation is 0.21 cm ≤ 10 cm and the settlement rate is 0.68 < 2 cm/year. This shows that improvements can increase the SF value and reduce settlement.